Examining adherence to activity monitoring devices to improve physical activity in adults with cardiovascular disease: A systematic review. (March 2019) - Marin, Tania S; Kourbelis, Constance; Foote, Jonathon; Newman, Peter; Brown, Alex; Daniel, Mark; Coffee, Neil T; Nicholls, Stephen J; Ganesan, Anand; Versace, Vincent L; Beks, Hannah; Haedtke, Christine A; et al.
Background: Activity monitoring devices are currently being used to facilitate and monitor physical activity. No prior review has examined adherence to the use of activity monitoring devices amongst adults with cardiovascular disease. Methods: Literature from June 2012 to October 2017 was evaluated to examine the extent of adherence to any activity monitoring device used to collect objective physical activity data. Randomized control trials comparing usual care against the use of an activity monitoring device, in a community intervention for adults from any cardiovascular diagnostic group, were included. A systematic search of databases and clinical trials registers was conducted using Joanna Briggs Institute methodology. Results: Of 10 eligible studies, two studies reported pedometer use and eight accelerometer use. Six studies addressed the primary outcome. Mean adherence was 59.1% (range 39.6% to 85.7%) at last follow-up. Studies lacked equal representation by gender (28.6% female) and age (range 42 to 82 years). Conclusion: This review indicates that current research on activity monitoring devices may be overstated due to the variability in adherence. Results showed that physical activity tracking in women and in young adults have been understudied.